“No Face Can Be Approached With Empty Hands and Closed Home”: Literacy in the Post-Truth Era - Parker, Lana (Journal of the Canadian Association for Curriculum Studies, 2020)
Education has a responsibility to respond to the threat of deteriorating democracies (DeLuca & Christou, 2016; Peters, 2017). The post-truth era is marked by an erosion of trust in public institutions and conflict in online spaces. The broad purpose of this research is to examine the ways in which the evolving post-truth era has the potential to redefine how people consume information and make decisions, and to explore the implications for democracy. A more specific purpose is to draw attention to the limits of current literacy pedagogy and to propose a literacy education that engages deeply with questions of intersubjectivity. I begin with a discussion of the evolution of literacy education policy and curriculum, looking at disjunction between research and practice. I demonstrate the ways current literacy and media literacy education is not simply outmoded, but also limited by neoliberal conceptions of rationality and individualism. Offering a counterpoint to the status quo, I work with Levinas’ (1969, 1989) conception of ethics to consider the importance of three affective dimensions of literacy. I illustrate the tensions between affective reactionism and non-intentional affectivity, enjoyment and its disruption as a premise for intersubjectivity and two manifestations of anger—moral and defensive. I conclude with a proposal for literacy education that furnishes a space for the intersubjective relation to emerge. This approach comprises an intentional focus on relationality, responsibility and affect.